The Gathering Gloom 2007-2009 (Vol. 07) - Ikram Sehgal (Karachi, Pakistan Pathfinder Group, 2021)
Articles on the economy and politics in Pakistan covering the period July 2007 to August 2009.
Include Illustrations and Index
Keywords: Economy and Commerce -- Internal Policy -- Accountability and Corruption -- Foreign Relations and Policies -- Internal and External Security